Educação básica para todos: o acesso à educação como uma meta internacional - Felten, Milena Acosta (2015)
This research aims to analyze how the international standard setting process for basic education, established by international agents and widespread in developing countries, are implemented and investigated in Brazil. To accomplish this goal the international project Millennium Development Goals established by the United Nations in 2000 is analyzed in its objective on universal basic education. Considering how that goal was developed in Brazil is possible to reflect about the way education is understood and presented by such programs. The Critical Theory of Society grounds the bases for this discussion, especially the concepts of Education, Formationa and Pseudo formation developed by Adorno. Other authors such as Horkheimer and Marcuse were also used to discuss how the universalization of education relates to the right to education. The research was conducted through document analysis, checking how these objectives have been translated into Brazilian schools reality. The data presented in official reports of the international project quoted are analyzed in three categories: access, permanency and programs and policies. Due to the exploratory nature of the research, initial hypotheses have not been formulated. In conclusion, the access to education has been widely discussed in the Brazilian official reports, in disregard to the permanency aspects or data, and the extension of the basic education length from eight to nine years has been one of the main, however not the only, direct political measure derived from the Develop Millennium Goals project